EVALUASI SISTEM PENGENDALIAN INTERNAL BUMDES B KABUPATEN MAGETAN SEBAGAI UPAYA MENGHINDARI KECURANGAN - Nika Kartika Sari; Supri Wahyudi Utomo; Elana Era Yusdita (RISTANSI: Riset Akuntansi, 2025)
This study was conducted with the aim of evaluating the internal control system that has been implemented in BUMDes B, Magetan Regency. In this research, the researcher used a qualitative descriptive method. The results of this study, based on the COSO framework, indicate that: (1) there is no organizational structure, resulting in an unclear separation of duties and authorities; (2) a risk assessment has been carried out for the livestock business unit during the current year, but no risk assessment has been conducted for the online payment business unit; (3) there is no activity control in the online payment business unit; (4) there is no clear information and communication system in the online payment business unit; (5) there is no monitoring activity in the online payment business unit. Based on these weaknesses, several improvements are needed, such as establishing a new organizational structure and clarifying the division of main tasks in each section; creating new policies that clarify transaction flows and facilitate the preparation of financial reports; communicating information regarding the new policies and building effective communication; and supervising each business unit to minimize the occurrence of fraud.